Polymer Gels Science and Fundamentals (Gels Horizons: From Science to Smart Materials,, 2018)
This book exclusively focuses on the science and fundamentals of polymer gels, as well as the numerous advantages that polymer gel-based materials offer. It presents a comprehensive collection of chapters on the recent advances and developments in the core science and fundamentals of both synthetic and natural polymer-based gels, and pays particular attention to applications in the various research fields of biomedicine and engineering. Key topics addressed include: polysaccharide-based gels and their fundamentals; stimuli-responsive polymer gels; polymer gels applied to enzyme and cell immobilization; chitosan-based gels for cancer therapy; natural polymeric and gelling agents; radiation dosimetry; polymeric gels as vehicles for enhanced drug delivery across the skin; transport in and through gel; and polymer gel nanocomposites and functional gels. The book's extensive and highly topical coverage will appeal to researchers working in a broad range of fields in industry and academia alike.